The multifaceted roles of embryonic microglia in the developing brain - Hattori, Yuki (Frontiers in Cellular Neuroscience, 2023)
Microglia are the resident immune cells of the central nervous system (CNS). Microglia originate from erythromyeloid progenitors in the yolk sac at the early embryonic stage, and these progenitors then colonize the CNS through extensive migration and proliferation during development. Microglia account for 10% of all cells in the adult brain, whereas the proportion of these cells in the embryonic brain is only 0.5–1.0%. Nevertheless, microglia in the developing brain widely move their cell body within the structure by extending filopodia; thus, they can interact with surrounding cells, such as neural lineage cells and vascular-structure-composing cells. This active microglial motility suggests that embryonic microglia play a pivotal role in brain development. Indeed, recent increasing evidence has revealed diverse microglial functions at the embryonic stage. For example, microglia control differentiation of neural stem cells, regulate the population size of neural progenitors and modulate the positioning and function of neurons. Moreover, microglia exert functions not only on neural lineage cells but also on blood vessels, such as supporting vascular formation and integrity. This review summarizes recent advances in the understanding of microglial cellular dynamics and multifaceted functions in the developing brain, with particular focus on the embryonic stage, and discusses the fundamental molecular mechanisms underlying their behavior.